PENGGUNAAN INTERNET TERHADAP PENINGKATAN PARTISIPASI POLITIK DAN KEHIDUPAN DEMOKRASI - Reny Yuliati (Universitas Bunda Mulia, 2016)
Internet is a medium that become increasingly in demand by society from different circle. With the Internet as new media brings some changes on how people can voice their aspirations. The purpose of this article is to look at the advantages of new media in enhancing political participation and democracy compared with traditional media. With the new media, we have a great hope in democracy in Indonesia as long as government and citizens use it wisely. Keywords: new media, democracy, political participation